High-mobility transparent conductive layers based on indium oxide doped with tungsten - A.K. Akhmedov; A.Sh.. Asvarov; E.K. Murliev; Z.V. Shomakhov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
Increasing the conductivity of transparent conductive layers by increasing the mobility of free charge carriers is one of the most important tasks of transparent electronics, since its solution contributes not only to the reduction of heat losses in the layers, but also to the expansion of the spectrum of the radiation used towards the near infrared region. Currently, work in this area is being carried out in some routes, one of which is the search for new layer’s compositions that allow reducing the amount of impurity introduced while simultaneously increasing the efficiency of its ionization. In this paper, the influence of the oxygen content in the working gas and the deposition temperature on the morphology, microstructure, electrical, and optical characteristics of thin layers deposited by high-frequency magnetron sputtering of an ceramic target based on In2O3 with the addition of 1 wt.% WO3 was investigated. It was found that the maximum mobility (59 cm2/V٠s) and minimum specific resistance (7,8×10–4 Ohm٠cm) are achieved in layers synthesized at 300°C in the pure argon atmosphere. For comparison, layers based on a solid solution of indium and tin oxides, widely used in the formation of transparent electrodes in various optoelectronic applications, were obtained under identical conditions. It was shown that layers based on indium oxide doped with tungsten retain acceptable transparency in a wide spectral range, up to 2000 nm, and are, therefore, preferable for use in devices operating in the near infrared range, for example, in solar energy converters or night vision devices.